Acetylcholinesterase Choline-Based Ionic Liquid Inhibitors: In Vitro and in Silico Molecular Docking Studies - Siopa, Filipa (2020)
COMPETE Programme: SAICTPAC/0019/2015 IF/00780/2015 Project no. 022161